Integrity of the N-terminal transcription domain of p53 is required for mutant p53 interference with drug-induced apoptosis - Matas, Devorah (Oxford University Press, 2001)
The present study examined whether the ability of mutant p53 to block apoptosis depended on its transcriptional activity. A core domain mutant p53 (143 Val to Ala), in which two N-terminal residues (22 and 23) essential for transactivation were also mutated (Leu to Glu and Trp to Ser, respectively), was examined. While p53 containing only the core mutation efficiently interfered with drug-induced apoptosis, further modification at the N-terminus abolished this blocking activity. Furthermore, expression of c-myc, a suggested target for core mutant p53 transactivation, was elevated in the core mutant p53-expressing cells, but was abolished in the presence of the transcription-deficient p53 core mutant. In addition, wild-type p53, mutated in the N-terminus (residues 22 and 23), was unable to induce apoptosis by itself. Nevertheless, it synergized with drugs in the induction of apoptosis. This suggests that the integrity of the N-terminus is essential for both the activity of wild-type p53 in apoptosis and for mutant p53-mediated block of drug-induced apoptosis. This supports the notion that core p53 mutants act via a gain of function mechanism.